2011
DOI: 10.1557/opl.2011.1466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sn Substitution on the Thermoelectric Properties of Nanostructured Bulk Bi2-xSbxTe3 Alloy.

Abstract: The carrier concentration and electronic transport properties in Bi 2-x Sb x Te 3 alloy can be tuned by varying the Bi to Sb ratio, for high thermoelectric figure of merit. The concentration of intrinsic antisite defects in these alloys is also known to change with Bi to Sb ratio. Here we report the thermoelectric figure of merit of Sn doped Bi 0.5 Sb 1.5 Te 3 alloy. Different atomic percentages of Sn was substituted at Bi/Sb site in Bi 0.5 Sb 1.5 Te 3 alloy, synthesized by planetary ball milling. The electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Several dopants such as In (PE = 1.78) or Ga (PE = 1.81) [ 33,34 ] have been shown to effectively suppress the antisite defects in Sb 2 Te 3 and despite the fact that In and Ga belong to the group III elements, both act as donors. The case of Sn (PE = 1.96) in Sb 2 Te 3 is more complex since its amphoteric character was reported by Santhanam et al, [ 35 ] even though Kulbachinskii et al [ 36 ] have only reported an acceptor character in single crystals. At low Sn contents (below 2 at.%), Sn acts as a donor while at doping levels higher than 3 at.% Sn acts as an acceptor.…”
Section: Doi: 101002/aelm201400008mentioning
confidence: 95%
“…Several dopants such as In (PE = 1.78) or Ga (PE = 1.81) [ 33,34 ] have been shown to effectively suppress the antisite defects in Sb 2 Te 3 and despite the fact that In and Ga belong to the group III elements, both act as donors. The case of Sn (PE = 1.96) in Sb 2 Te 3 is more complex since its amphoteric character was reported by Santhanam et al, [ 35 ] even though Kulbachinskii et al [ 36 ] have only reported an acceptor character in single crystals. At low Sn contents (below 2 at.%), Sn acts as a donor while at doping levels higher than 3 at.% Sn acts as an acceptor.…”
Section: Doi: 101002/aelm201400008mentioning
confidence: 95%
“…Conserving energy through efficiency carries the twin benefits of not only decreasing pollution from coal but also lowering production costs of manufactured goods, thus allowing a higher standard of living through cleaner air while saving businesses money. However, available thermoelectric materials are impractical for large-scale production or widespread use because of the synthetic complexity, the lengthy time required for preparation, the incorporation of toxic or rare elements, or the low efficiency as rated by the dimensionless figure of merit, ZT = T α 2 /(ρκ tot ) . The parameters comprising ZT (Seebeck coefficient, α; electrical resistivity, ρ; and total thermal conductivity, κ tot , which itself is the sum of electronic charge carrier (κ C ) and lattice (κ L ) contributions) couple unfavorably, making the realization of large ZT values, a considerable challenge to materials scientists.…”
Section: Introductionmentioning
confidence: 99%